2015
DOI: 10.1080/13602381.2015.1020649
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national distance and insidership within networks: Japanese MNCs' ownership strategies in their overseas subsidiaries

Abstract: This study investigates the controversial question about how cross-national distance influences MNCs' equity ownership in their overseas subsidiaries. Prior studies adopted aggregated constructs and time-invariant measures of cross-national distance, failing to capture the complexity of the phenomenon. Moreover, although 'insidership' within business networks may moderate the foreignness that MNCs confront in overseas markets, prior studies have not incorporated it into analysis. The present study confirms the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
3
9
1
Order By: Relevance
“…On the distance dimensions, it can be seen that administrative distance had a negative and statistically significant effect (p=0.0543) on Portuguese inward FDI. This result is in line with previous research (Bailey & Li, 2015;Duarte & Carvalho, 2018;Zhang, 2015), as well as with finding by reports on Portugal's attractiveness to FDI (e.g. EY, 2017,2018), where legal constraints are highlighted as factors deterring FDI into the country.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…On the distance dimensions, it can be seen that administrative distance had a negative and statistically significant effect (p=0.0543) on Portuguese inward FDI. This result is in line with previous research (Bailey & Li, 2015;Duarte & Carvalho, 2018;Zhang, 2015), as well as with finding by reports on Portugal's attractiveness to FDI (e.g. EY, 2017,2018), where legal constraints are highlighted as factors deterring FDI into the country.…”
Section: Resultssupporting
confidence: 93%
“…Lastly, political distance revealed a positive and significant impact (p=0.0342). Although previous research found negative and non-significant effects of political distance on FDI outflows (Bailey & Li, 2015;Zhang, 2015), we believe that an internalization perspective could explain our results. To the extent a MNE perceive the political environment in the host country to be increasingly uncertain, the more likely it internalizes its foreign operations in order to exert greater control rather than depending on foreign agents (Buckley & Casson, 1998;Rugman, 1980).…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Similarly, the impact of cultural distance on equity ownership decisions is also found to be ambiguous. Some studies argued that firms facing greater cultural distance try to reduce their level of ownership in an unfamiliar environment (Piaskowska & Trojanowski 2014; Rajan & Pangarkar 2000; Yamin & Golesorkhi 2010; Zhang 2015), while others suggested that firms prefer a higher degree of ownership to enter a culturally distant country because higher cultural differences create communication barriers in sharing the routines of the firm's headquarters and its competencies with the foreign venture, which may restrict synergistic gains from IJV (Padmanabhan & Cho 1996). In a meta‐analysis conducted by Tihanyi et al.…”
Section: Determinants Of Equity Ownership Decisions: Theoretical Frammentioning
confidence: 99%
“…In fact, Malhotra et al (2009), using a CAGE framework, found positive relationships of administrative and economic distances with the number of crossborder acquisitions by developing countries' multinational firms. On another study, Zhang (2015) found that several dimensions of crossnational distance were positively related to Japanese firms' levels of ownership in foreign affiliates.…”
Section: Introductionmentioning
confidence: 95%